CONSTRUCTION OF PISTON OUTER PROFILE FOR ROTARY TYPE EXPANSION MACHINE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The article discusses methods for constructing piston outer profile for the rotary type expansion machine in order to reduce unwanted (parasitic) volumes and offers options for constructing outer profile of piston using analytical and geometric methods.